Controlled availability of opioids: a feasibility study, 1991 - Bammer, Gabrielle (ADA Dataverse, 2019)
The aim of this study was to explore the issues surrounding a suggested trial of controlled availability of opioids in the ACT. The study involved four different surveys, designed to elicit the views of the general community, police, service providers and drug users/ex-users. All four questionnaires surveyed perceptions of what constitutes a drug problem, attitudes to taking various drugs, awareness of the proposal for a controlled availability trial, support for the suggested trial, and opinions about how the trial should be conducted. In addition, the community survey asked whether any close person has been an illegal drug user or affected by drug-related crime, and asked about personal experience of drug-related illness or other problems. The police survey covered involvement with drug-related matters in police work, opinions about drugs in relation to crime (e.g. which drug is most responsible for crime, effectiveness of current police policy, extent of drug-related crime in the ACT, penalties for drug-related crime, drug-related corruption in the police force), beliefs about the effect of the proposed trial on police, and detailed opinions about procedures for the proposed trial and effects of the trial. Community service providers were asked about the main function of their service, proportion of clients under18 years, treatment philosophy, perceived effectiveness of various treatments, detailed opinions about procedures for the proposed trial and effects of the trial, and personal experience with drugs. Drug users and ex-users were asked about drug usage among friends and co-habitants, current drug use, treatment for heroin/opiate use (intended, current or past treatment), means of raising money for drugs, driving under the influence of drugs, drug-related violence, opinions about the suggested trial, interest in being placed on the trial, and perceived personal effects of the trial. Background variables covered by all four surveys were sex, year of birth, age at leaving school, level of education, whether the respondent has children under 25 years old, and whether the respondent currently practices a religion. Additional background variables for the police survey were length of time in the police force, current employment status, area of police work, length of time in current section, and current rank. Background variables for the service providers survey included current employment status and occupation. Background variables for the drug users/ex-users survey included employment status, current living situation, and residential mobility.